If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7(-2y + -9) + 2(-6y + 4) = 0 Reorder the terms: -7(-9 + -2y) + 2(-6y + 4) = 0 (-9 * -7 + -2y * -7) + 2(-6y + 4) = 0 (63 + 14y) + 2(-6y + 4) = 0 Reorder the terms: 63 + 14y + 2(4 + -6y) = 0 63 + 14y + (4 * 2 + -6y * 2) = 0 63 + 14y + (8 + -12y) = 0 Reorder the terms: 63 + 8 + 14y + -12y = 0 Combine like terms: 63 + 8 = 71 71 + 14y + -12y = 0 Combine like terms: 14y + -12y = 2y 71 + 2y = 0 Solving 71 + 2y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-71' to each side of the equation. 71 + -71 + 2y = 0 + -71 Combine like terms: 71 + -71 = 0 0 + 2y = 0 + -71 2y = 0 + -71 Combine like terms: 0 + -71 = -71 2y = -71 Divide each side by '2'. y = -35.5 Simplifying y = -35.5
| 60+25x=35x+29 | | e^2k=3 | | 4x^4-9x^2-100=0 | | 8u-2=2u+8 | | 9-8p-8=45 | | -4y+14=-22 | | 9r+4=4+9r | | 57.95m=50.45m+60 | | W*(w+4)=60 | | 4(6x-10)=20 | | 50.45m+60=57.95 | | 2x+3(2x+11)=129 | | 4x^2+16x+32=0 | | log(x)=0.137 | | 6-n=-n+2 | | m^2+2m-36=0 | | 4x+3(x-18)=30 | | 3x^2-24x=45 | | 6t-17-4t=10 | | 4y+32=11+6y | | 6x+10=20x-8 | | 4*(n+1)=32 | | 3(8+8x)+6= | | 4k-(7+k)=-(8k+7) | | -x-14=6+3x | | 3m=3m+5 | | 6x+4(6x-12)=132 | | -21=-7/5v | | 4z+9=8 | | -3x+23=5 | | 5p+5(-5-3p)= | | 2x+2x-14=x+9+x+2+x-7 |